Effect of continuous application of organics to supply nitrogen and phosphorus on maize (Zea mays) and chickpea (Cicer arietinum) under irrigated condition - RAJKUMARA, S; GUNDLUR, S S; KHOT, A B (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted at Water Management Research Centre, Belavatagi during 2004–09 for six years to study the effect of nutrients applied through organics and inorganics. Application of nitrogen either 75% or 100% through organics in maize was not sufficient in sustaining the maize grain yield. Application of 100% inorganics fertilizer + 10 tonnes FYM/ha (5.95 tonnes/ha) gave significantly higher grain yield over all other organics and organics + inorganics treatment. In chickpea, application of 100% P through inorganics gave higher chickpea yields (1.349 tonnes/ha) and was on par with 50% organics + 50% inorganics (1.277 tonnes/ha) and this indicated organics may reduce inorganics in the long run. Economic parameters were significantly higher in 100% inorganic treatment. Addition of organics either 75% or 100% improved the organic carbon and other physical properties of the soil over inorganics treatment.